PENGARUH KECERDASAN EMOSIONAL, KARAKTERISTIK PEKERJAAN DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KOTA PADANGSIDIMPUAN - Roni Mukti Siregar; Leonard Simorangkir; Satria Ginting; Rahmad Amin Angkat; Eni Ery Yanti (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
The Formulation In this research is how emotional intelligence influences, job characteristics and workload on the performance of The Education Officer In Padangsidimpuan City, and the purpose of this research is to know and analyze the influence of emotional intelligence, work characteristics and workload on the performance Of The Education Officer Of Padangsidimpuan City. This research is a quantitative descriptive study. Data collection techniques are conducted through interviews, inquiry lists and documentation studies. The samples in this study were as many as 39 employees. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The Results of the test in unison showed that emotional intelligence, occupational characteristics and workload demonstrated a very noticeable influence on the performance of The Education Officer In Padangsidimpuan City with the value Fcount 16,464 Ftable 2.85 and significance value of 0.000b. Adjusted number of R Square by 0. 550 or (55%) Show that the percentage of contributions influence independent variables (emotional intelligence, occupational characteristics and workload) to the dependent variables (employee performance) by 55%. Partially, emotional intelligence was positively influential in the performance of The Education Officer In Padangsidimpuan City with a value of tcount ttable (4,444 2,022) and a significance value of 0. 000. The characteristics of the work positively and significantly affect the performance of The Education Officer In Padangsidimpuan City with the value Tcount ttable (2,600 2,022) and the significance value of 0. 014. The workload was negatively and significantly influential on the performance of The Education Officer In Padangsidimpuan City with a value of tcount ttable (-3,287 2,022) and a significance value of 0. 002. The highest value of a regression coefficient is the emotional intelligence (X1) of 0. 497 or 49.7% and is the most dominant variable affecting the performance of The Education Officer In Padangsidimpuan City.